MENELAAH KORUPSI DAN DEMOKRASI DI INDONESIA - INDRA FAUZAN (Universitas Sumatera Utara, 2012)
Corruption is a big problem in coutries around the world. Corruption is a issues which are prevalent in developing countries and country’s transition to democratie. In many research studies claim that Indoensia is one of the most corrupt countries. After reform, Indonesian democration have made much progress, unfortunetly, in the body of democratie, corruption grow and flourish, and thus causing the country suffered great losses. This study explore about relation between corruption and democracy. Collecting data is using library research. The finding is the corruption occurs in every agency of government or non government, even occurs in the institution of the democracy itself, namely political parties and representative institutions of the people. Democracy is supposed to be a way out for the creation of a corruption-free country, but now democracy even an entrance for corruption. Strong need for comprehensive reform and strengthen the democratic system a clean and healty, and reduce the corruption of democracy in the body.Keywords: Corruption, democracy, political system.